Time perspective and place of residence: An empirical study - SENYK, OKSANA M. (Journal of Education Culture and Society, 2020)
The article focuses on relationship between time perspective and place of residen-ce. Five hundred and eleven Ukrainian participants completed the Zimbardo Time Per-spective Inventory [Ukrainian language version by Oksana Senyk (Senyk, 2012)] and a questionnaire that included the question about participants’ current place of residence and their place of residence in childhood. Answers to the questionnaire made it possible to consider in the research respondents’ change of residential place and its relation to the formation of different time orientations. The results have shown that the individu-al’s time perspective is influenced not by the specific life situation represented by his past or current place of residence, but upon his whole life story that includes changing different residential settlements. The research has also indicated that among all types of settlements rural settlements most significantly contribute to the development of time orientation towards a positive past.